Speaking Anxiety of the Eleventh-Grade Students at Senior High School - Khalisya; Shynta Amalia; Rizqy Dwi Amrina (Didascein : Journal of English Education, 2024)
Anxiety related to speaking can also impair students' communication skills; students who have poorly understood pronunciation feel ashamed and are unwilling to practice speaking. This research was conducted to determine the categories of anxiety of the speaking anxiety level by the eleventh-grade students in the English classroom of SMAN 19 Palembang. This descriptive research used a quantitative descriptive method. The research instrument was a questionnaire. The questionnaire was adapted from the Foreign Language Speaking Anxiety Questionnaire (FLSAQ) from Öztürk and Gürbüz (2014). This research involved 76 students of eleventh grade in the English classroom of SMAN 19 Palembang. It consisted of 17 statements with three categories: high level, medium level, and low level. The collected data was analyzed using descriptive analysis. Based on the research analysis, it was found that the dominant speaking anxiety was test anxiety. The types faced by the respondents were the fear of test anxiety (75.62%), communication apprehension (73%), and fear of negative evaluation (70.04%). Furthermore, from the questionnaire result, the anxiety level category was determined to be 3 categories: high level, medium level, and low level. The level of students’ speaking anxiety in the middle level was 56.6%. It is significantly different from other levels with 32.9% for the low level and 10.5% for the high level. This finding indicated that teachers need to be more aware of students’ anxiety to arouse students’ motivation to speak confidently and fluently in English-speaking classes. Therefore, teachers must be creative in designing better techniques to encourage students to talk more.